Real-Time Monitoring and Control System of Water Parameters for Paiche Cultivation - Beraún Espíritu, Manuel Michael (2024)
The arapaima, also known as paiche or pirarucu is one of the largest freshwater fish in the Amazon, in which its cultivation has been growing progressively due to consumer demand. This research presents the design of a real-time monitoring and control system of water parameters for paiche farming, which employs mechatronics concepts using the Vdl- 2206 methodology. The study controls and monitors the water's temperature, dissolved oxygen, and pH. Sensors obtain the values for each parameter, process them by a PLC, and project them on an HMI interface. The environment is programmed based on the information provided by FONDEPFS, which mentions that the water temperature for paiche cultivation must be between 26ºC to 31°C, the pH leve! between 6 and 8 UI, and dissolved oxygen with a value greater than or equal to 4 mg/L. In addition, the proposed mechatronic system aims to be a user-friendly sy,tem, where the primary function is the monitoring and controlling water parameters for paiche cultivation, resulting in the correct functioning of the systen thus concluding the feasibility of implementation and the contribution to the development of new research.